What Determines the Speed of Adjustment to the Target Capital Structure? - Wolfgang Drobetz; Gabrielle Wanzenried (University of Basel, Center of Business and Economics (WWZ), 2004)
We use a dynamic adjustment model and panel methodology to investigate the determinants of a time- varying optimal capital structure. Because firms may temporarily deviate from their optimal capital structure in the presence of adjustment costs, we also endogenize the adjustment process. In partic ular, we analyze the effects of firm-specific characteristics as well as macroeconomic factors on the speed of adjustment to the target leverage. Our sample comprises a panel of 90 Swiss firms over the years 1991 to 2001. We find that faster growing firms and those that are further away from their optimal capital structure adjust more readily. Our results also reveal interesting interrelations between the adjustment speed and popular business cycle variables. For example, the speed of adjustment is higher when the term spread is higher, i.e., when economic prospects are good.
Keywords: G32; C23; E44; 330; Capital structure; dynamic adjustment; business cycle; panel data